(untitled) (Revista de História Regional, 2007)
Language, text and memory are part of the basic material with which the historian works. They circulate in the limits between the theoretical and methodological reference, but in the hermeneutic perspective, such objects let themselves be known in the same scope of the language. In this text, we try to investigate the interpretative movement that confers sense to these terms, investigating the motion picture Star gate and the eighth chapter of Jacques Le Goffs History and memory .